Progression and regression of kidney disease in type 1 diabetes - Jansson Sigfrids, Fanny; Groop, Per-Henrik (Frontiers in Nephrology, 2023)
Diabetic kidney disease is distinguished by the presence of albuminuria, hypertension, declining kidney function, and a markedly elevated cardiovascular disease risk. This constellation of clinical features drives the premature mortality associated with type 1 diabetes. The first epidemiological investigations concerning type 1 diabetes-related albuminuria date back to the 1980s. The early studies found that proteinurialargely equivalent to severe albuminuriadeveloped in 35 to 45% of individuals with type 1 diabetes, with the diabetes duration-specific incidence rate pattern portraying one or two peaks. Furthermore, moderate albuminuria, the first detectable sign of diabetic kidney disease, was found to nearly inexorably progress to overt kidney disease within a short span of time. Since the early reports, studies presenting more updated incidence rates have appeared, although significant limitations such as study populations that lack broad generalizability, study designs vulnerable to substantive selection bias, and constrained follow-up times have been encountered by many. Nevertheless, the most recent reports estimate that in modern times, moderateinstead of severealbuminuria develops in one-third of individuals with type 1 diabetes; yet, a considerable part (up to 40% during the first ten years after the initial albuminuria diagnosis) progresses to more advanced stages of the disease over time. An alternative pathway to albuminuria progression is its regression, which affects up to 60% of the individuals, but notably, the relapse rate to a more advanced disease stage is high. Whether albuminuria regression translates into a decline in cardiovascular disease and premature mortality risk is an area of debate, warranting more detailed research in the future. Another unclear but alarming feature is that although the incidence of severe albuminuria has fallen since the 1930s, the decline seems to have reached a plateau after the 1980s. This stagnation may be due to the lack of kidney-protective medicines since the early 1980s, as the recent breakthroughs in type 2 diabetes have not been applicable to type 1 diabetes. Therefore, novel treatment strategies are at high priority within this patient population.